Mutational activation of the epidermal growth factor receptor down‐regulates major histocompatibility complex class I expression via the extracellular signal‐regulated kinase in non–small cell lung cancer. Issue 1 (27th November 2018) - Watanabe, Satomi; Hayashi, Hidetoshi; Haratani, Koji; Shimizu, Shigeki; Tanizaki, Junko; Sakai, Kazuko; Kawakami, Hisato; Yonesaka, Kimio; Tsurutani, Junji; Togashi, Yosuke; Nishio, Kazuto; Ito, Akihiko; et al.
Abstract : The efficacy of programmed cell death–1 (PD‐1) blockade in patients with non–small cell lung cancer (NSCLC) positive for epidermal growth factor receptor (EGFR) gene mutations has been found to be limited, but the underlying mechanisms for this poor response have remained obscure. Given that the recognition by T cells of tumor antigens presented by major histocompatibility complex class I (MHC‐I) molecules is essential for an antitumor immune response, we examined the effects of EGFR tyrosine kinase inhibitors (TKIs) on MHC‐I expression in NSCLC cell lines. Appropriate EGFR‐TKIs increased MHC‐I expression at the mRNA and cell surface protein levels in NSCLC cells positive for EGFR mutations including those with the T790M secondary mutation. Trametinib, an inhibitor of the extracellular signal–regulated kinase (ERK) kinase MEK, also increased MHC‐I expression, whereas the phosphatidylinositol 3‐kinase (PI3K) inhibitor buparlisib did not, suggesting that the MEK‐ERK pathway mediates the down‐regulation of MHC‐I expression in response to EGFR activation. Immunohistochemical analysis of EGFR ‐mutated NSCLC specimens obtained before and after EGFR‐TKI treatment also revealed down‐regulation of phosphorylated forms of EGFR and ERK in association with up‐regulation of MHC‐I, an increased number of infiltrating CD8 + T cells, and increased PD‐1 ligand 1 expression after such treatment. Our results thus suggest that mutational activation of EGFR inhibits MHC‐I expression through the MEK‐ERK pathway in NSCLC and thereby contributes to the poor response of such tumors to immunotherapy. Further studies are warranted to evaluate the relation between EGFR‐MEK‐ERK signaling in and the immune response to EGFR ‐mutated NSCLC.  Abstract : Mutational activation of EGFR inhibits MHC‐I expression through the MEK‐ERK pathway in NSCLC and thereby may contribute to the poor response of such tumors to immunotherapy.